Surface wave-induced Eulerian-mean flows in the open ocean - Higgins, CJ (2020)
This thesis examines Lagrangian-mean flows induced by surface gravity waves, with particular emphasis on the displacements associated with these flows. Stokes drift, the small Lagrangian-mean velocity accompanying the orbital motion of particles beneath surface waves, has been well-studied, and is proven to play a role in ocean transport. However, Eulerian-mean flows induced by slow variation of the wave field (divergence-driven), viscous effects, or geophysical effects such as density stratification and planetary rotation, have received less attention. It is the aim of this thesis to study these wave-induced Eulerian-mean flows, which must be superimposed on the Stokes drift to obtain the correct Lagrangian-mean (or mass transport) velocity induced by surface gravity waves. In Chapter 2, the effects of wave directional spread and density stratification on the mean flow induced by a surface gravity wavepacket in deep water are studied, and the corresponding displacements are derived. Chapter 3 examines ‘Ekman–Stokes’ dynamics driven by the Stokes drift and Coriolis force within the turbulent upper ocean boundary layer, and uses buoy data to explore the impact these dynamics have on the drift of a floating particle. Finally, in Chapter 4 I combine the insights of the two previous chapters to develop an analytical model capable of describing both divergence-driven and geophysically-driven Eulerian-mean flows induced by surface waves.